TRANSMITTING CHARISMA: Re-reading Weber through the Traditional Islamic Leader in Modern Java - Achmad Zainal Arifin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
This paper tries to reconsidering the theory of authority, propounded by Max Weber, a pioneer of classical theory of sociology, particularly on his idea of charisma. Weber predicted that modernisation, as represented by the rationalisation process which is unstoppable phenomena for modern world lead the changing process of charismatic authority into other forms of authorities, especially the legal-rational one. By describing the dynamics of Kyai’s charismatic authority within the pesantren milieu, the rationalisation process tends to enhance the existence of charismatic authority of kyai. Based on a case study of a famous traditional pesantren in Yogyakarta, this paper elaborates the process of rationalisation describes how all instruments of traditional pesantren, including those that are resulted from the process, have contribution in preserving and maintaining the charismatic authority o kyai. Most members of traditional pesantren even believe that the quality of charisma, which is laid on the foundation of supernatural power, can be transmitted to the next successor through the institutionalisation of practices to gain that power.